2014
DOI: 10.1534/genetics.114.168948
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Influences on Brain Gene Expression in Rats Selected for Tameness and Aggression

Abstract: Interindividual differences in many behaviors are partly due to genetic differences, but the identification of the genes and variants that influence behavior remains challenging. Here, we studied an F 2 intercross of two outbred lines of rats selected for tame and aggressive behavior toward humans for .64 generations. By using a mapping approach that is able to identify genetic loci segregating within the lines, we identified four times more loci influencing tameness and aggression than by an approach that ass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(28 citation statements)
references
References 98 publications
1
27
0
Order By: Relevance
“…We also identified plexin-b2-like, which in mammals is involved in several processes during development of the nervous, cardiovascular, renal, and skeletal system (Worzfeld et al, 2014). Another plexin from the same subfamily has been associated with behavior-related traits, such as tameness and temperament in rat and cattle (Friedrich, Brand, & Schwerin, 2015;Heyne et al, 2014). This finding is in line with the identification of the gene autism susceptibility 2 protein-like and both suggest that domestication could be acting on behavior-related traits.…”
Section: Biological Function Of Nonparallel Genomic Regions Identifsupporting
confidence: 84%
“…We also identified plexin-b2-like, which in mammals is involved in several processes during development of the nervous, cardiovascular, renal, and skeletal system (Worzfeld et al, 2014). Another plexin from the same subfamily has been associated with behavior-related traits, such as tameness and temperament in rat and cattle (Friedrich, Brand, & Schwerin, 2015;Heyne et al, 2014). This finding is in line with the identification of the gene autism susceptibility 2 protein-like and both suggest that domestication could be acting on behavior-related traits.…”
Section: Biological Function Of Nonparallel Genomic Regions Identifsupporting
confidence: 84%
“…Albert FW et al mapped the locations of DNA sequence differences (quantitative trait loci; QTL) that contributed to differences between the tame and aggressive rat lines (Albert et al, 2009). More recently, they also identified using mRNA sequencing and a QTL mapping method multiple genes influenced by the genetic variants from the tame and aggressive lines (Heyne et al, 2014). Candidate genes that may play a causal role in these behaviors have been implicated in anxiety and stress.…”
Section: Evidence For the Existence Of Gamentioning
confidence: 99%
“…Successful territory defence via aggression can be a key determinant of fitness, but aggression can also be costly in terms of time, energy and the risk of injury (Huntingford et al, 1987). Studies in diverse organisms from fruit flies (Dierick & Greenspan, 2006; Wang et al, 2008; Edwards et al, 2009; Shorter et al, 2015) to mice (Sluyter et al, 1995) and rats (Heyne et al, 2014) and chickens (Buitenhuis & Kjaer, 2008) have shown that there is a heritable component to aggressiveness, and have suggested that aggressiveness is influenced by thousands of loci. Aggressiveness is also influenced by the early environment (Arnold & Taborsky, 2010), including the environment provided by parents (Curno et al, 2009; Bentz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%